Effect of micro-scale wind on the measurement of airborne pollen concentrations using volumetric methods on a building rooftop. (June 2017) - Miki, Kenji; Kawashima, Shigeto; Fujita, Toshio; Nakamura, Kimihito; Clot, Bernard
Abstract: Evaluating airborne pollen concentrations is important for the understanding of the spatiotemporal dispersion of pollen grains. Using two identical pollen monitors in parallel, we performed two experiments in order to study the influences of a) the physical characteristics (orientation) of the air inlet and b) the presence of obstacles in proximity to the monitors on airborne pollen concentration data. The first experiment consisted of an evaluation of airborne pollen concentrations using two different types of orifices; 1) a vertically oriented inlet and 2) a wind vane intake, both attached to the same type of automatic pollen sampler. The second experiment investigated the relationship between vertical wind speed and horizontal wind direction around an obstacle with the goal of studying the impact of micro-scale wind on pollen sampling efficiency. The results of the two experiments suggest that the wind path near an obstacle might be redirected in a vertical direction before or after the wind flows over the obstacle, which causes measurement errors of airborne pollen concentrations that are proportional to the vertical wind speed, especially when a vertically oriented inlet is used. Graphical abstract: Highlights: Airborne pollen concentrations were evaluated using two types of inlets. Horizontal wind direction and vertical wind speed around an obstacle was studied. An obstacle alters the wind path causing errors in pollen concentration data.